Itinerários de cuidado de si de mulheres trabalhadoras sexuais da Barra do Ceará - Silva, Lorena Brito da (2022)
This thesis is about the care practices that circulate among women and the rationalities that support them, considering their itineraries through the territories of prostitution and the neighborhood of Barra do Ceará, Fortaleza/CE. To analyze the production of self-care itineraries, it was necessary to know intersectionally the experiences of care, map the main networks of relationships with other people, places and services. Furthermore, personal and collective care practices were related to each other, questioning the rationalities that support them. Theoretically-methodologically, Foucauldian, decolonial and black feminism studies supported this qualitative research. Barra do Ceará was the reference territory, and based on the project “Take care!” three areas of prostitution were visited (trottoir, massage parlor and bar area), marked by an impoverished territory, in conflict between factions and the police. Between 2017/19, interviews, field diaries, observations and conversations were carried out in everyday life, using discursive practices as a way of analyzing the 9 scenes that make up the study. The women are between 18 and 35 years old, non-white, with incomplete high school, single mothers who left home early, living in rooms close to battle points. As main learnings, the control images of “easy-life bitch”, “poor bitch” and “sassy bitch” were systematized as effects of racism, sexism and class prejudice that intensify precariousness, contributing to the weakening of bonds and loneliness. From a medical-legal articulation, public policies act more in the control and prevention of STI transmission. The Community Health Agents approach the sex workers, however, the expanded teams find it difficult to continue the follow-ups started in the zone. Their care itineraries are limited to zones, mainly involving the points where they cultivate oldest relationships, as well as in an Umbanda terreiro that offers spiritual and physical care. The “Take care!” mediated the approximation with UAPS, CUCA and CAPS, and the recreational spaces are in the zones and in the relatives' houses. Care practices were systematized into 3 groups: a) Do to yourself: anonymity as a guarantee of privacy and survival; b) health care: recognition of when to leave or stay in the area; seek baths, teas and prayers before heading to public facilities; c) Establishment of alliances in the territories: camaraderie and intimacy mark when relationships go beyond the zone; mutual care when facing pain; relationships with cafetinas/pimps and fixed customers will be alliances of learning and protection; the zone as a place of work, celebration and resistance. It is considered that the self-care, when betting on an ethical relationship with the exercise of doing the self, can contribute to the integrality and the creation of practices that are in tune with their ways of living. The dispute between biomedical-colonial, biopsychosocial, community-traditional andzone-comradeship rationalities goes beyond health care, crossing the conditions/authorizations to exist. It is expected to contribute with integral and plural care practices in prostitution zones.